2016
DOI: 10.1177/194849921600700104
|View full text |Cite
|
Sign up to set email alerts
|

Music Educator Views on String and/or Orchestral Participation in Alabama, Arkansas, Louisiana, and Mississippi

Abstract: The purpose of this study was to discover music educators' views on string music education by surveying active NAfME members in Alabama, Arkansas, Louisiana, Mississippi, and to compare results based on teaching area: string/ orchestra (SO) and non-string/orchestra (NSO). While statistically we cannot generalize results because of the response rate and numbers of SO and NSO teachers in our study, those who responded to our online survey support our hypothesis that fewer string/orchestra programs exist in our f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Insufficient budget, scheduling difficulties, lack of administrative support, and a shortage of highly qualified music teachers were pointed out as major inhibiting factors. All of these reasons were proposed to be the main negative factors for the development of string programs in schools in previous studies (Abril & Gault, 2008;Gillespie & Hamann, 2010;Kuehne & Harrison, 2016). Strong parental and administrative support, sufficient funding, scheduling, and quality music teachers, on the other hand, were identified as promoting factors, which is also in accordance with findings of previous studies (Gillespie & Hamann, 2010).…”
Section: Qualitative Results Discussedsupporting
confidence: 86%
See 2 more Smart Citations
“…Insufficient budget, scheduling difficulties, lack of administrative support, and a shortage of highly qualified music teachers were pointed out as major inhibiting factors. All of these reasons were proposed to be the main negative factors for the development of string programs in schools in previous studies (Abril & Gault, 2008;Gillespie & Hamann, 2010;Kuehne & Harrison, 2016). Strong parental and administrative support, sufficient funding, scheduling, and quality music teachers, on the other hand, were identified as promoting factors, which is also in accordance with findings of previous studies (Gillespie & Hamann, 2010).…”
Section: Qualitative Results Discussedsupporting
confidence: 86%
“…Tast (2014) reported that 13% of school districts in Kansas offered string instruction, that 95% of orchestra teachers were White, and that 75% of teachers indicated a string instrument as their primary instrument. Kuehne and Harrison (2016) investigated music educators' views on the state of string/orchestra programs in four focus states: Alabama, Arkansas, Louisiana, and Mississippi. The findings suggested a teachers' perception that fewer school orchestra programs exist in these four states than in other parts of the country.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These concerns may lead to a vital question: Can the current professional pipeline supply the demand for new string teachers? The current body of research suggests not (Hamman et al, 2002; Kuehne & Harrison, 2016; Schimek, 2002).…”
mentioning
confidence: 97%